Exploring The Use of Traditional Games to Stimulate Critical Thinking in The Context of Early Life Skills - Sri Tatminingsih M.PD; Erna Risnawati (Universitas Pendidikan Ganesha, 2026)
Critical thinking skills and life skills are essential competencies that need to be developed from early childhood; however, learning strategies that are capable of integrating both competencies in a holistic manner remain limited. This study aims to explore strategies for developing critical thinking skills in the context of early childhood life skills through the use of traditional games. This research employs a Research and Development (R&D) approach consisting of nine developmental stages, with a focus on the initial stage, namely needs analysis. The research subjects involved early childhood education teachers selected through cluster random sampling. Data were collected through questionnaires and structured interviews, and then analyzed using descriptive quantitative and simple qualitative analysis. The findings indicate that traditional games have strong potential as learning media because they contain life values that can stimulate children’s critical thinking skills and life skills. Effective learning strategies to optimize this potential include the use of guiding questions, providing opportunities for children to explain their thinking, implementing open ended storytelling games, practicing simple problem solving tasks, offering challenging activities, and conducting self evaluation activities. The conclusion of this study confirms that traditional games can be integrated into learning as structured and contextual pedagogical media. The implication of this study highlights the importance of integrating traditional games into early childhood education curricula to support the sustainable development of critical thinking skills and life skills.